2012
DOI: 10.3340/jkns.2012.51.5.316
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Toxoplasmosis Combined with Disseminated Tuberculosis

Abstract: A 24-year-old man presented with mental change, fever, abdominal pain, tenderness and palpable mass on the lower abdomen. He was a non-Korean engineer and did not accompany a legal guardian, so medical history taking was difficult due to his mental status. Brain magnetic resonance imaging showed multiple rim-enhanced lesions of the brain, and abdominal computed tomography showed huge paraspinal abscess. Chest X-ray and computed tomography showed poorly defined nodular opacities. We initially thought that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…They concluded about the awareness of the fact that toxoplasmosis can occur in immunocompetent patients and coincide with any other infection such as TB. Our case reiterates the suggestion by Hwang et al 22 by describing the codetection of pulmonary TB and toxoplasmosis. The finding of AFB positivity in a respiratory sample may dissuade the cytopathologist from searching further for a coexisting pathology.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They concluded about the awareness of the fact that toxoplasmosis can occur in immunocompetent patients and coincide with any other infection such as TB. Our case reiterates the suggestion by Hwang et al 22 by describing the codetection of pulmonary TB and toxoplasmosis. The finding of AFB positivity in a respiratory sample may dissuade the cytopathologist from searching further for a coexisting pathology.…”
Section: Discussionsupporting
confidence: 92%
“…Significantly higher level of MDA was shown to depict serious illness in case of coinfection among TB/Toxoplasma coinfected patients as compared to Toxoplasma negative TB patients. Hwang et al 22 reported a case of 24‐year‐old male patient of confirmed cerebral toxoplasmosis along with features of disseminated TB. They concluded about the awareness of the fact that toxoplasmosis can occur in immunocompetent patients and coincide with any other infection such as TB.…”
Section: Discussionmentioning
confidence: 99%
“…About 17 parasite genera concurrent with M. TB were reviewed as case reports, epidemiological surveys and immunological research, which were divided into protozoa ( Entamoeba [32,49], Leishmania [8-16,31], Giardia lamblia [28,32], Trichomonas [17], Plasmodium [18,33,35,37,38], Toxoplasma [19-21]) and helminths ( Clonorchis sinensis [30], Opisthorchis [39,40], Schistosoma [22,33,34], Taenia [32], Echinococcus [23-27], Ascaris lumbricoides [32,34,49], Toxocara [20], Trichuris trichiura [30,32,34], Ancylostoma [32-34], Strongyloides stercoralis [28,32,34,49], Filaria [29,43,44]) and covered most of the common parasites species. Of those, leishmaniasis, hydatid disease and malaria were reported to coexist more freuequently with TB in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…First, socio-demographics, such as gender and age as previously mentioned above, maybe relate to prevalence of co-infection. Second, some special patients, such as renal transplant recipients, patients on maintenance haemodialysis, HIV positive patients and migrants [8,10-12,14,16,21,22,28,33], are likely to be susceptible populations of co-infection. Last but not least, there are higher probabilities of co-infection in some areas with a higher prevalence of TB and parasitic diseases, such as India and East Africa [11,12,16,18,23,29,31-34].…”
Section: Discussionmentioning
confidence: 99%
“…The second case we found is of a four-year-old girl in Sri Lanka who had a co-infection of TB, toxoplasma, and toxocara which was confirmed by biopsy of inguinal TB lymphadenopathy, serum toxoplasma IgM, and serum toxocara IgG [ 11 ]. The third case reported was from South Korea, with an immunocompetent Indonesian worker who had disseminated TB and cerebral toxoplasmosis [ 12 ]. In developing countries, because of the high prevalence of TB and lack of diagnostic accessibility, some physicians raised the concern about a misleading diagnosis of toxoplasmosis in patients who had TB or lymphoma.…”
Section: Discussionmentioning
confidence: 99%